(untitled) (Research, Society and Development, 2025)
Objective: To synthesize scientific evidence on the effectiveness of physiotherapy protocols applied before and after coronary artery bypass grafting (CABG) surgery. Methodology: Narrative review of the literature conducted in the PubMed, PEDro, SciELO, Lilacs, and Cochrane databases between 2010 and 2025, in English and Portuguese. Randomized clinical trials, systematic reviews, and meta-analyses that evaluated physiotherapy rehabilitation protocols in the pre- and/or postoperative period of CABG were included. After screening and evaluation, 11 studies remained (eight RCTs and three reviews/meta-analyses). Results: Physiotherapy protocols applied at different stages of cardiac rehabilitation after coronary artery bypass grafting (CABG) vary significantly in approach, intensity, and duration. Pre-rehabilitation with aerobic and respiratory exercise protocols promoted significant gains in functional and cardiorespiratory capacity and reduced hospital stay. In phase I (intra-hospital), protocols combined with aerobic exercise, early mobilization, and respiratory training improved functional capacity and pulmonary function and reduced hospital stay. In phase II (outpatient), the combination of aerobic and resistance exercise associated with inspiratory muscle training brought improvements in functional and cardiorespiratory capacity with the potential for sustained gains. Conclusion: Physical therapy is essential and safe in post-myocardial revascularization rehabilitation, with robust evidence in phase I (in-hospital) and promising evidence in pre-rehabilitation. In phase II (outpatient), there is a lack of robust evidence, compromising the continuity of benefits and the evaluation of long-term outcomes.